Dracula’s mistress: removal of blood-red floral nectar results in secretion of more nectar - Thomas Mione; Isaac Diaz (Plant Ecology and Evolution, 2020)
Background and aims – Flowers of Jaltomata quipuscoae (Solanaceae) secrete blood-red nectar that serves as an energy reward and possible attractant to pollinators. The purposes of this study were to determine whether simulated pollinator visits (manual removal of nectar) stimulates replenishment of nectar, and report the pattern of nectar presentation during the lifespan of the flower. Methods – For the nectar replenishment experiments flowers were paired: each pair of flowers was selected to be on the same plant and at the same developmental stage. From all 62 flowers nectar was removed and discarded (not measured) at time zero. Then, over a period of eight hours, the nectar of one flower was measured four times, i.e., every two hours, while nectar of the paired control flower was measured only at the end of the eight-hour period. In the nectar dynamics experiment five sets of flowers received different treatments: flowers were unmanipulated for zero, one, two, three or four days and then nectar was removed once every day. The volume of nectar produced and concentration of sugar in the nectar were recorded at each extraction for both studies.Key results – In the nectar replenishment study significantly higher nectar volume and consequently significantly higher total sugar content was present in the experimental nectar-extracted flowers. In the nectar dynamics study, nectar was produced starting on day one or two, continuously through the life of the open flowers until one or two days before the corolla senesced. Delay of nectar removal from different flower sets for zero, one, two, three or four days resulted in a linear increase in nectar volume and total nectar sugar production, and had little or no effect on the cumulative (life of the flower) nectar production. Floral longevity, seven to ten days, was not affected by a single removal of nectar each day.Conclusions – The floral nectary of J. quipuscoae responded to nectar removal by secreting more nectar, and thus more total sugar (not a higher concentration of sugar) than was secreted by control flowers. In flowers from which nectar was not removed, nectar volume and thus total sugar secreted continued to accumulate linearly, suggesting that reabsorption of nectar either does not occur or is slow relative to the rate of secretion. The more we (or pollinators) take, the more the flowers make: the volume of nectar and sugar production increase if nectar is removed frequently but not if nectar is removed infrequently.